Leadership expectations: how executive expectations are created and used in a non-profit setting. - Early, Gene (Regnum studies in mission., 2005)
Leadership Expectations is an in-depth study that focuses on how one leader creates and uses expectations to shape a university, its culture, and its success. This research operates on the underlying assumption that the organization is an expression of the leader and the people they attract. As the personal, interpersonal, and organizational agendas a leader carries in their mind and enacts in their behavior are understood, the organization can be understood. Concurrently, at least one major means of organizational transformation emerges: executive development. The result: the leader's personal development, and/or lack of it, drives organizational performance. The cost: the leader's self-sacrifice energizes the values they most deeply hold for themselves, others, and the university they lead. The reward is truth revealed about themselves, others, and their organization: lives are touched and transformed, and organizational capacity for good increases.